Effectiveness of tenofovir or telbivudine in preventing HBV vertical transmission for pregnancy - Zeng, Jianyong (Medicine (Baltimore), 2019)
To evaluate the efficacy and safety of telbivudine (LdT) and tenofovir (TDF) for preventing hepatitis B virus (HBV) vertical transmission for HBV-positive pregnant women. Pregnant women (n = 145) from January 2013 to June 2017 were enrolled when they met inclusion criteria, which included HBV DNA ≥1.0 × 10(7) copies/mL and increased alanine aminotransferase (ALT) levels. Groups A (n = 58) and B (n = 51) were treated with LdT and TDF, respectively. Group C (n = 36) received no antiviral treatment. All infants were vaccinated with hepatitis B immunoglobulin and HBV vaccine. Vertical transmission of HBV was indicated by the presence of hepatitis B surface antigen (HBsAg) in infants 6 months and 12 months after birth. There is no difference of clinical characteristics of patients among the 3 groups. Serum HBV DNA levels of the 3 groups were similar at baseline (Group A vs. Group B vs. Group C, 7.88 ± 0.65 vs. 7.91 ± 0.75 vs. 7.69 ± 0.53 P = .25). In addition, the after anti-HBV treatment in Groups A and B were significantly decreased. Also, the serum HBV DNA levels in both Groups A and B were lower than that of Group C (P < .01, both). The HBV infection rate in Group A treated with LdT was not different from Group B treated with TDF. The dynamic changes of serum ALT level were similar. ALT levels were similar among the 3 Groups (P = .171), while there is statistically significant difference between A and C, and between B and C before delivery (P < .01). For the infants, there were no significant differences among body weight, height, head circumference, or Apgar score. However, the HBsAg positivity rates of infants in Groups A, B, C at postpartum 24 weeks and 48 weeks was 0%, 0%, and 11.1%, respectively (P < .001). Administration of LdT or TDF to HBV-infected mothers are effective and safe to block mother-to-infant HBV transmission.